Redox Kinetics and Mechanism of the Reactions of µ –Oxobis [aquobis (2,2’ – Bipyridine)] diruthenium (III) Ion and some Aliphatic Alcohols in Acidic Medium (Lafia Journal of Scientific and Industrial Research, 2024)
The redox kinetics and mechanisms of the reactions of μ – oxobis[aquobis(2,2’ - bipyridine)]diruthenium (III) ion, [(bipy)2(H2O)RuORu(H2O)(bipy)2]4+ (hereafter denoted as Ru2O4+ or [(H2O)2(bipy)4Ru2O]4+) and some primary aliphatic alcohols was studied in perchloric acid medium, [H+] = 5.0 x 10-3 mol dm-3, ionic strength (I), = 0.5 mol dm–3 (NaClO4), temperature (T) = 31 ± 1°C and  wavelength ,λmax =  660 nm. The reactions, which led to the formation of corresponding aldehydes had a stoichiometry of 1:1, were all first order with respect to each reactant, and second order overall. The reactions proceeded in the absence of acid but when acid was added, the reactions ceased. Varying the ionic strength and dielectric constants of the reaction medium had no effect on the reaction. Added ions catalysed the reaction and free radicals were identified in the reaction mixtures in the course of the reactions. There was no evidence for the formation if intermediate complex in the course of the reaction. The order of reactivity is of the order CH3OH > C2H5OH > C3H7OH Based on the  results, it is suggested that all the reactions proceeded through the outer – sphere electron transfer mechanism and a plausible mechanism that represented all the reactions is proposed.
Keywords: dielectric constant; free radicals; ionic strength; rate constant; stoichiometry